2022
DOI: 10.21468/scipostphys.12.5.174
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic, noise-induced dynamics in the Anderson insulator

Abstract: We study the dynamical behavior of the one-dimensional Anderson insulator in the presence of a local noise. We show that the noise induces logarithmically slow energy and entanglement growth, until the system reaches an infinite-temperature state, where both quantities saturate to extensive values. The saturation value of the entanglement entropy approaches the average entanglement entropy over all possible product states. At infinite temperature, we find that a density excitation spreads logarithmically with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…We would like to remark that a rigorous analytical derivation supporting the logarithmic growth of the density profile in the outer regime remains an open and challenging problem. In relation to this we note a recent interesting work in [39] in a much simpler setup involving a single local dephasing connected to an Anderson insulator. This work reported an interesting logarithmic spread in time of density excitation.…”
Section: Localized Phase λ/J>1mentioning
confidence: 73%
See 2 more Smart Citations
“…We would like to remark that a rigorous analytical derivation supporting the logarithmic growth of the density profile in the outer regime remains an open and challenging problem. In relation to this we note a recent interesting work in [39] in a much simpler setup involving a single local dephasing connected to an Anderson insulator. This work reported an interesting logarithmic spread in time of density excitation.…”
Section: Localized Phase λ/J>1mentioning
confidence: 73%
“…For example, it was recently shown that for a one-dimensional disordered lattice, displaying Anderson localization, when subjected to a local dephasing, density excitation spreads logarithmically in time [39]. Very recently, this study involving dephasing probes was extended for the incommensurate Aubrey-Andre-Harper (AAH) lattice model [40].…”
Section: J Stat Mech (2024) 063101mentioning
confidence: 99%
See 1 more Smart Citation
“…A localized system is typically a closed system with no transport. Coupling a localized system to a Markovian heat bath induces slow transport for local coupling 55 , 56 or diffusive transport for global coupling 57 61 . A similar effect is expected to occur if a Markovian bath is replaced by a sufficiently large thermalizing system.…”
Section: Discussionmentioning
confidence: 99%
“…Khemani et al [28] showed nonlocal response to local manipulations in localized systems. Lezama and Bar Lev [29] studied the dynamics of an AL system with local noise. These works consider time-dependent Hamiltonians, and are thus different from ours.…”
mentioning
confidence: 99%